Fingerprint of the first stars: multi-enriched extremely metal-poor stars in the TOPoS survey - Hartwig, Tilman; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Extremely metal-poor (EMP) stars in the Milky Way inherited the chemical composition of the gas out of which they formed. They therefore carry the ch